WAYS TO IMPROVE THE MECHANISM OF PROPERTY INSURANCE IN THE REPUBLIC OF UZBEKISTAN - Sh.F. Kobilzhonova (Antis Publisher, 2024)
The article is devoted to the essence of insurance and the mechanism of realization of property insurance at the present stage of economic development in the Republic of Uzbekistan. Insurance is an important element of the functioning of the financial system of the state, capable of ensuring the continuity of social reproduction, depending on the negative consequences of natural disasters, accidents, natural and man-made disasters and other unforeseen events that cause high risks of property loss, as well as to guarantee social protection of the population. to stabilize the process of investing in the economy. Today, property insurance in Uzbekistan is an insurance industry in which the object of insurance relations are property interests and property in various forms (for example, buildings, structures, equipment, and so on). The property insurance market in our country is developing quite rapidly, and if there are no serious turning points in society in the future, then after a while insurance may become one of the main factors protecting the interests of citizens and legal entities owning any property.